Aligning technology with learning theories: A simulator‐based training curriculum in surgical robotics. Issue 3 (13th September 2013) - Alimisis, Dimitris; Zoulias, Emmanouil
Abstract : Purpose: – The aim of this research is the development of a problem‐based curriculum for robotic surgical training and its evaluation. Design/methodology/approach: – First, the aim and objectives of the curriculum are defined and the background learning theories that guide our work are introduced. The methodology for designing the simulator‐based training is presented and finally the output of this work is reported, that is the SAFROS training paradigm, resulted as a balanced synthesis of behavioural and constructivist learning theories. Findings: – The evaluation of basic skills tasks of the curriculum revealed a high acceptance among the trainees. Research limitations/implications: – Within this paper, a first implementation and evaluation of the basic skills tasks is described. Further cooperation between pedagogues and software engineers is required in order to put in practice the whole curriculum. Then, further training experiments with surgeons are necessary to check the validity of the whole curriculum. The authors also need to establish proficiency criteria that can come from the achievements of expert surgeons using the simulator and the robot and use them as final goals to be achieved by trainees in future courses. In the field of subjective evaluation, a possible future extension might be a bigger number of questions. Moreover, the innovative method of text mining in its application to opinion mining decisions can be further applied. Originality/value: – In this paper, an innovative approach for the development of a simulator‐based curriculum for robotic surgical training is presented and first evaluation results based on ratings from trainees are also presented. The value of this paper is relevant to medical trainers and curriculum designers.